2009
DOI: 10.3382/ps.2008-00496
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin directly increases adrenocorticotropic hormone-stimulated corticosterone production in the hen adrenal gland

Abstract: The present study was performed to elucidate whether the receptor for calcitonin (CT) exists in the adrenocortical cells of hens and to determine the effect of CT on adrenocorticotropic hormone (ACTH)-stimulated corticosterone production in its cell. The binding site of CT in the membrane fraction of the adrenal gland in hens was determined using a [125I]CT binding assay system. The binding properties in the adrenal gland satisfied the criteria of a receptor-ligand interaction in terms of specificity, reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…It has been reported that CT enhances the maximal secretion of ACTH stimulated by corticotropinreleasing hormone in the hen anterior pituitary (Nakayama et al 2010a), and increases corticosterone production stimulated by ACTH in the hen adrenal gland (Nakagawa-Mizuyachi et al 2009). The concentration of corticosterone in blood increases at the time of oviposition (Rice et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CT enhances the maximal secretion of ACTH stimulated by corticotropinreleasing hormone in the hen anterior pituitary (Nakayama et al 2010a), and increases corticosterone production stimulated by ACTH in the hen adrenal gland (Nakagawa-Mizuyachi et al 2009). The concentration of corticosterone in blood increases at the time of oviposition (Rice et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Anterior pituitary cells were incubated in vitro using the same method as reported earlier on the incubation of adrenocortical cells of the hen (Nakagawa‐Mizuyachi et al . 2009).…”
Section: Methodsmentioning
confidence: 99%
“…1999). Recently, it has been shown that the receptor for CT exists in the chicken adrenal gland and CT directly increases corticosteone production stimulated by adrenocorticotropic hormone (ACTH) through its receptor (Nakagawa‐Mizuyachi et al . 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Receptors for calcitonin (Nakagawa-Mizuyachi et al, 2009) and PTHrP (Kawashima et al, 2005) exist in the chicken adrenal gland, and these hormones directly increase corticosterone production stimulated by ACTH through their receptors. Recently, it was reported that calcitonin enhances the secretion of ACTH from the anterior pituitary via its receptor (Nakayama et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%